Effects Of Air Inlet Angle On The Combustion And Emission Characteristics Of A Cylindrical Chamber Fueled With Waste Cooking Oil Blends - Ong, Guan Kai (Universiti Sains Malaysia, 2022)
The scarcity of fossil fuels had greatly prompted a thorough search for alternative renewable resources. Diesel fuel made of petroleum could be replaced with biodiesel, an alternative energy source. One of the main constituents in biodiesel fuels is esters which are made of vegetable or animal fats. They are regarded as effective, healthy, and natural energy alternatives for fossil fuels. However, vegetable oil or waste cooking oil (WCO) is less combustible and possess higher viscosity compared with pure diesel. Larger droplets are generally produced due to the poor atomization quality. These droplets will burn slowly because of the shorter ignition delay. In addition, poor atomization characteristics of WCO will lead to poor air-fuel mixing. The poor air-fuel mixing results in bad performance of combustion and emission. Therefore, swirl motion is introduced to improve air-fuel mixing by creating an intense turbulent recirculation zone. The inlet angle affects the air motion inside the combustion chamber. A cylindrical combustion chamber with two tangential air inlets were created. The effects of air swirling with tangential air inlet angles of 0°, 10°, 20°, 30° and 45° were investigated using Ansys Fluent with a model of species transport. The mass flow rate of air and fuel are the same for all models to compare the effects of swirl motion better. The temperature and velocity profiles as well as the mass fraction of O2, CO2 and pollutant NO are comprehensively evaluated. Over the range of tangential air inlet angles examined, the optimal angle was discovered to be 45°. The combustion chamber with tangential angle of 45° emitted the least pollutants of NO. Furthermore, it was also found that kerosene is slightly better than WCO fuel in terms of combustion and emissions characteristics. The viscosity and cetane number of kerosene is lower than that of WCO fuel so that it is comparatively poor in atomization and vaporization characteristics. This phenomenon has resulted in lower emissions of CO2 and pollutant NO. However, WCO fuel can be an alternative resource of energy as it is renewable and biodegradable. It also has similar combustion performance with the conventional fuel.